MELANCHOLIA: SELF-REPRESENTATION IN CYBERCULTURE THROUGH DIGITAL ILLUSTRATION - Lunar Nengahing Ndalu (Eduarts: Jurnal Pendidikan Seni, 2025)
This article examines the relationship between Generation Z, cyberculture, and the expression of melancholia in the context of digital illustration art. As a member of Generation Z, the researcher experiences the dynamics of identity between the real world and the virtual world, both reflecting contrasting aspects of personality. Using a practice-based research approach, this article explores two digital illustrations that represent melancholy: one depicts the positive and reflective side of the real world, while the other depicts the dark and distorted side of cyberspace. The analysis is conducted through an aesthetic and visual content approach, drawing on color theory, visual semiotics, and the context of cyberculture. The results of the creation and analysis demonstrate that digital illustration functions not only as a medium for visual expression but also as a contemplative space for addressing the psychological and existential realities of Generation Z. This article also emphasizes the importance of understanding the virtual world as an integral part of the identity formation of the digital generation.